Comparative Analysis of Low Molecular Weight Vs Unfractionated Heparin in Surgical Patients Receiving DVT Prophylaxis - Monsif Iqbal, Shabab Hussain, Abdul Wahid, Khan Karim, Viqar Aslam, Muhammad Nasir, Faisal Khan, Inam Ullah (Pakistan Journal of Medical & Health Sciences, 2022)
Aim : To evaluate low molecular weight heparin and unfractionated heparin in prophylaxis of venous thromboembolism in terms of post operative haemorrhage in surgical patients. Study design: Randomized control trail study Place and duration of duty: Surgical Department, POF Hospital Wah Cantt and DHQ Teaching Hospital KDA Kohat from 7th September 2018 to 7th March 2020. Methodology: Two hundred patients of moderate risk for venous thromboembolism were included in the study and divided into groups 1&2. Group 1 patients were receiving low molecular weight heparin and group 2 on unfractionated heparin. Patients in both groups were observed for post operative haemorrhage at 1st, 2ndand 3rd postoperative day. Results: Post operative haemorrhage from surgical wound was noticed in a single patient of group 1 and 11 pts of group 2. Conclusion: The chances of post operative haemorrhage are less in patient receiving Low molecular weight heparin in contrast to unfractionated heparin in prevention of venous thrombosis and embolism in surgical patients